Immunoexpression of HER family, neuregulin, MAPK and AKT in invasive ductal carcinomas of the breast - (:unkn) unknown (My University, 2008)
Background:The purpose of this study was to investigate the frequency of expression of the erbB/HER family of growth factor receptors, their ligand neuregulinalpha (NRGalpha) and the most important pathways activated by HER receptors that are mitogen-activated protein kinase (MAPK) and serine/threonine kinase (AKT) in invasive ductal carcinomas of the breast, not otherwise specified (IDC-NOS).Methods:59 of the IDC-NOS of the breast were studied for ER, PR, EGFR, c-erbB-2, c-erbB-3, c-erbB-4, neuregulin Ab-3, phospho-AKT, and phospho-p44/42 map kinase using the streptavidin-biotin horseradish method.Results:Of the 59 tumours, 44 (75%) were ER+, 37 (63%) PR+, four (7%) EGFR+, seven (12%) c-erbB-2+, seven (12%) c-erbB-3+ and 14 (24%) c-erbB-4+alpha. Strong cytoplasmic and/or nuclear immunoexpression was revealed in 17 (29%) cases for NRGalpha, 13 (22%) cases for p-AKT, and nuclear immunoexpression with p-MAPK was found in 17 (29%) cases.Conclusion:The results suggest that high-grade breast carcinomas are not only associated with ER/PR- negativity, but seem to be activated by receptor tyrosine kinase growth factors.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Cerrahi Tıp Bilimleri; Patoloji; Sitoloji; Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Surgery Medicine Sciences; Pathology; Cytology; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; CERRAHİ; TIBBİ BİLİŞİM; TIP, GENEL & DAHİLİ; PATOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; SURGERY; MEDICAL INFORMATICS; MEDICINE, GENERAL & INTERNAL; PATHOLOGY; Histoloji; Patoloji ve Adli Tıp; Aile Sağlığı; Temel Bilgi ve Beceriler; Cerrahi; Tıbbi Bilişim; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Histology; Pathology and Forensic Medicine; Family Practice; Fundamentals and Skills; Surgery; Health Informatics; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine